The art of chalk techniques & inspiration for creating art with chalk - Stum, Tracy Lee (Rockport Publishers, 2016)
Chalk, a ubiquitous and versatile implement made from limestone, is much more than a humble tool for jotting impermanent notes. With a wide range of uses in art and design, chalk is quickly becoming a favourite of artists around the world to create impressive works of art. In The Art of Chalk, noted street painter Tracy Lee Stum takes an inspiring look at the many exciting creative applications for this easily accessible medium. With a historic overview of chalk's origins as an art medium, and how its artistic uses have evolved over the centuries, this book is a wealth of knowledge for anyone looking to get creative with this time-honoured art medium.
Includes index. - Print version record
Keywords: Chalk drawing -- Technique; Pastel drawing -- Technique; Street art -- Technique; Dessin à la craie; Technique; Pastel; Technique; Art dans la rue; Technique; Pastel drawing; Technique; Street art; Technique